An Efficient and Ecofriendly Three-Component Reaction for the Rapid Synthesis of 2-Amino-4H-chromenes Catalyzed by a DABCO-Based Ionic Liquid - Li, Cheng-Bin; Li, Yu-Wei; Xu, Da-Zhen (Synthesis, 2018)
An efficient, economical, and green strategy for the construction of biologically relevant 2-amino-4H-chromene scaffolds via a tandem Knoevenagel–Pinner cyclization–Michael reaction has been successfully developed. In the presence of DABCO-based ionic liquids, two different 2-amino-4H-chromene derivatives, 2-amino-4-(indol-3-yl)-4H-chromenes and 2-amino-4-(pyrazol-4-yl)-4H-chromenes, were prepared in good to excellent yields (81–97%) within short reaction times under mild conditions. All the products are purified by simple crystallization. The catalyst could be recycled for at least five times.
Keywords: 2-amino-4H-chromene; green chemistry; ionic liquid; multicomponent reaction; salicylaldehyde